2015
DOI: 10.1002/chin.201520085
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: An Efficient Approach to the Synthesis of Hydrazinyl Pseudo‐Peptides.

Abstract: An Efficient Approach to the Synthesis of Hydrazinyl Pseudo-Peptides. -The novel hydrazinyl pseudo-peptides, obtained by an Ugi four-component reaction, possess high potential for H-bonding. -(FATHI, V.; RAMEZANPOUR, S.; BALALAIE*, S.; ROMINGER, F.; REZA BIJANZADEH, H.; Helv. Chim. Acta 97 (2014) 12, 1630-1637, http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Thayamini and Brintha (2010) noted that the planting pattern of maize and legume did not affect the maize yield. Also, Fathi (2014) concluded that nitrogen fertilizer application significantly increased the grain yields and above-ground biomass of maize at all rates of nitrogen application (30, 60 and 120 kg /fed) and the highest grain yield was recorded in maize + soybean intercropping with entire recommended rate of mineral nitrogen application.…”
Section: Maize Yield and Qualitymentioning
confidence: 98%
“…Thayamini and Brintha (2010) noted that the planting pattern of maize and legume did not affect the maize yield. Also, Fathi (2014) concluded that nitrogen fertilizer application significantly increased the grain yields and above-ground biomass of maize at all rates of nitrogen application (30, 60 and 120 kg /fed) and the highest grain yield was recorded in maize + soybean intercropping with entire recommended rate of mineral nitrogen application.…”
Section: Maize Yield and Qualitymentioning
confidence: 98%